Safe Sex Health Awareness: Knowledge and Attitudes Regarding Male Condom Protection Role against Sexually Transmitted Infections among Minia University Students, Egypt - Ekhlass M. Eltomy (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Condoms are beneficial in preventing certain infections but may not completely protect from other infections, such as AIDS due to having various transmission routes. Providing sex education, focused on enhancing knowledge and attitudes targeting the youth. The aim was to assess knowledge and attitudes regarding male condom protection role against sexually transmitted infections among Minia university students. Design: A quasi-experimental design with pre-posttest was utilized. Settings: conducted initially at faculties of science, literature and education, Minia University, then researcher followed them at staff Minia club. Tool:I- An interviewing socio demographic questionnaire. II- Knowledge and Attitudes questionnaire Results: The level of knowledge among the studied faculties had improved from 40.2 %, 88.9 & 28.2 % to 85.4, 100% & 91.3 % of literature, science and education faculties respectively post intervention. The attitude among the studied faculties had changed positively from 74.2 %, 100 % & 93.5 % of literature, science and education faculties’ pre intervention to 85.6 %, 100 % & 95.7 % post intervention respectively. Conclusion: the highest levels of knowledge were concerning AIDS the least reported one were concerning HPV. Students had a positive attitude and intentions towards limited and localized role of condom.